Growth of Carotid Intima‐Media Thickness in Black and White Young Adults. Issue 12 (20th December 2016) - Hao, Guang; Wang, Xiaoling; Treiber, Frank A.; Davis, Harry; Leverett, Sharika; Su, Shaoyong; Kapuku, Gaston
Abstract : Background: There are few longitudinal studies that have comprehensively examined the intima‐media thickness (IMT) growth pattern and its determinants among racial population groups. Methods and Results: Mean and maximum IMT were measured by B‐mode ultrasonography up to 3 times in 253 white and 268 black participants, aged 13 to 36 years (mean age±standard deviation 24±3.2 years old). The development of IMT was assessed using individual growth curve modeling. A total of 521 participants with 1015 IMT measurements were eligible for this study. We found higher IMT in both left and right sides in blacks compared to whites ( P <0.001) in young adulthood. Both whites and blacks showed a strong linear increase in mean IMT with age. Body mass index and father's education level were associated with mean IMT, and only body mass index was associated with maximum IMT ( P <0.05). We did not observe an interaction between age and race/ethnicity on the growth of IMT, suggesting that blacks and whites developed IMT in similar patterns. Interestingly, we found a faster increase in mean left‐side IMT than mean right‐side IMT (χ 2 =11.5, P <0.001) in both black and white subjects as well as in males and females. Conclusions: Our findings provide compelling prospective evidence that blacks may have thicker IMT compared to whites as young adults. These racial differences could not be explained by traditional risk factors. This implies that differences in this precursor of atherosclerosis may explain racial disparity in cerebrovascular disease.